The quantification of trademark damaged: a new three-step rule - Achard, Jorge (2017)
The objective of the present work is to further study the determination of trademark damages, studying our legislation as well as comparative legislation and the last relevant judgments in the matter, with the final aim of proposing a simple method that allows to establish basic criteria for its determination. The determination of trademark damages is usually one of the most complex obstacles to be overcome by trademark owners when initiating a claim for damages to those who used their trademark without authorization. The complexity of the subject and the jurisprudential doubts in the matter has led to an unnecessary saturation of the criminal system. This is why, at both the comparative and national levels, specific criteria have been established that can be used to determine trademark damage, depending on the assumptions in which we find ourselves. In the study of the local cases we have found four different classes of trademark infringements: 1. Sale of counterfeit that confused products with the original products: 2. Sale of counterfeit products that do not cause confusion with the original products; 3. Use of a trademark without authorization of the owner, in order to identify a product or service to be commercialized, without any original product or service; 4. Use of a trademark without authorization of the holder for purposes beyond the identification of a particular product or service. In order to determine the damage in each of the aforementioned hypotheses, it is necessary to use the different existing tools so far, such as property damage, extra-patrimonial damage and loss of income through a novel concept for us that is called "license hypothetical".